2015
DOI: 10.1021/cb500787b
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Complex Protein Metabolism in Live Organisms by Stimulated Raman Scattering Microscopy with Isotope Labeling

Abstract: Protein metabolism, consisting of both synthesis and degradation, is highly complex, playing an indispensable regulatory role throughout physiological and pathological processes. Over recent decades, extensive efforts, using approaches such as autoradiography, mass spectrometry, and fluorescence microscopy, have been devoted to the study of protein metabolism. However, noninvasive and global visualization of protein metabolism has proven to be highly challenging, especially in live systems. Recently, stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 41 publications
2
116
0
Order By: Relevance
“…Wei et al further improved the label incorporation using a mixture of 20 deuterated amino acids, and applied SRS for fast image acquisition 28 (Figure 2B–E). This methodology is later optimized into a general platform to interrogate protein metabolism across a variety of systems, including primary neuron cells, brain tissues, and even whole animals including zebrafish larvae and mouse 29 (Figure 2F and G). They revealed possibly function-related higher protein synthesis activity in hippocampus and cortical regions in a brain slice.…”
Section: Protein Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Wei et al further improved the label incorporation using a mixture of 20 deuterated amino acids, and applied SRS for fast image acquisition 28 (Figure 2B–E). This methodology is later optimized into a general platform to interrogate protein metabolism across a variety of systems, including primary neuron cells, brain tissues, and even whole animals including zebrafish larvae and mouse 29 (Figure 2F and G). They revealed possibly function-related higher protein synthesis activity in hippocampus and cortical regions in a brain slice.…”
Section: Protein Metabolismmentioning
confidence: 99%
“…By targeting carbon hydrogen bonds and carbon deuterium bonds respectively, they achieved ratiometric images between existing proteins and newly synthesized proteins, and identified newly grown neurites which had a higher percentage of newly synthesized proteins (Figure 5A). And in the follow-up study by the same group, where all 20 amino acids were replaced by their deuterium substituted counterparts in the custom-prepared media, the protein synthesis on an entire ex vivo organotypic brain slice was quantitatively visualized 29 . (Figure 5B) The authors found that the protein synthesis was only active in the dentate gyrus of the hippocampal region and in a few individual neurons.…”
Section: Brain Imaging and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Using SRS microscopy, Zhang et al (42) studied cellular lipid uptake using treatment with deuterated fatty acids. Deuterated compounds have also helped visualize important metabolites in cells, such as protein and choline (112, 116, 117). Shen et al (115) studied protein degradation in cells with carbon-isotope-labeled SRS imaging.…”
Section: Applications Using Crs Microscopymentioning
confidence: 99%
“…Deuterium-based Raman labels have been successfully used in nonlinear optical imaging applications to help increase specificity to water dynamics, 21 selected phospholipids, 22,23 neutral lipids, [24][25][26] and protein metabolism. 27,28 Labels based on stable isotopes, including deuterium, have found widespread use in clinical applications. Because the level of toxicity of pharmacological substances and their deuterated analogs is typically identical, deuterated substances are widely used in clinical studies aimed at studying the metabolism and movement of drugs in humans.…”
Section: Introductionmentioning
confidence: 99%